Fenomena Pelecehan Seksual Catcalling Dalam Kajian Sosiologi Gender - Yana, Rahmah Husna; Triyanto, Triyanto; Lestari, Rachmatika (Universitas Teuku Umar, 2025)
Catcalling is a term for the phenomenon of verbal teasing behavior that leads to sexual harassment experienced by women. For people in Indonesia, catcalling is behavior that is considered normal by society, so the catcalling phenomenon still occurs frequently. The sociological study analysis used in this research uses the theory of feminism and patriarchal culture. Furthermore, this research was carried out with descriptive qualitative research using the literature study method. From the results of the analysis of sociological studies, the catcalling phenomenon is a behavior that is considered to be culturally acceptable, even normalized due to the patriarchal culture that is still embedded in society's social life. and in the view of feminist theory, catcalling is behavior that disturbs women's comfort and existence in the public sphere.